Era Fintech: Peluang Dan Tantangan (Financial Technology) Syariah di Indonesia - M. Masykur Hadi; M. Firdausil Ulum; Ardi Surya; Aisah Aprillia S; Aulia Vivi F (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Apart from technological developments, the financial industry is also developing with the emergence of fintech (financial technology). Fintech is an innovation in the financial sector that refers to modern technology. Increasing the presence of fintech which leads to the emergence of sharia-based fintech and providing convenience to customers will certainly have an impact on the formal sharia financial industry. Modern online businesses are replacing traditional businesses, and Indonesia is one of the leading leaders in fintech development. The Islamic financial industry is more stable and viable than the conventional financial industry. The aim of this research is to identify opportunities and challenges for Indonesian Sharia fintech (financial technology). The data analysis technique used is a qualitative technique and the results of this study show that there are opportunities and challenges for Sharia Fintech in Indonesia.